Brand Image and Service Quality in Tugboat Operations : A Case of TB Maiden Central - Marihot Simanjuntak; Akhmad Gifari Multazam; A. Nurfajri Irwan; Fitri Mulyana; Aji Permana (International Forum of Researchers and Lecturers, 2025)
This study investigates the relationship between brand image and service quality in maritime towage operations, using TB Maiden Central of PT. Multi Jaya Samudra as a case study. The research employs a descriptive quantitative approach supported by qualitative thematic analysis. Data were collected from 100 respondents through questionnaires and interviews with stakeholders including ship agents, pilots, and company personnel. Results show that brand image significantly influences service quality, with a positive impact reaching 79.8%. Key determinants include safety reputation, operational timeliness, professionalism, and environmental stewardship. The qualitative analysis highlights how visible safety practices and punctual operations reinforce brand credibility. Beyond statistical findings, the study reveals that trust and reliability play a central role in shaping customer perceptions, with stakeholders emphasizing the importance of transparent communication and consistent service delivery. Moreover, environmental responsibility, such as reducing emissions and complying with green port initiatives, strengthens the company’s image in the eyes of global partners. The integration of quantitative and qualitative insights provides a more holistic understanding of how operational performance directly influences market competitiveness through brand positioning. Findings contribute to maritime management scholarship by extending service quality frameworks into towage contexts, while also offering practical implications for enhancing competitiveness and sustainability. Overall, the study underscores the urgency of aligning brand image with operational excellence to meet rising global standards in maritime services and ensure long-term business growth.